TREATMENT OUTCOMES OF PHARMACOLOGICAL CLOSURE OF PATENT DUCTUS ARTERIOSUS IN PRETERM INFANTS AT THE NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the incidence of patent ductus arteriosus in preterm infants and to evaluate the effectiveness of pharmacological closure of the ductus arteriosus in preterm neonates at the National Hospital of Obstetrics and Gynecology.Method: This retrospective and prospective descriptive study included 267 preterm infants born at
Keywords: Patent ductus arteriosus, hemodynamically significant patent ductus arteriosus, Ibuprofen, Paracetamol, preterm infants.